2014
DOI: 10.1186/2191-219x-4-14
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the radiolabelling properties of technetium tricarbonyl and His-tagged proteins

Abstract: BackgroundTo date, the majority of protein-based radiopharmaceuticals have been radiolabelled using non-site-specific conjugation methods, with little or no control to ensure retained protein function post-labelling. The incorporation of a hexahistidine sequence (His-tag) in a recombinant protein can be used to site-specifically radiolabel with 99mTc-tricarbonyl ([99mTc(CO)3]+). This chemistry has been made accessible via a technetium tricarbonyl kit; however, reports of radiolabelling efficiencies and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…The formation of the 99m Tc tricarbonyl was monitored by TLC on glass-backed silica gel 60 plates developed with 1% HCl in methanol 20. The R f values in this system are as follows: 99m Tc tricarbonyl, 0.2–0.8; 99m Tc colloids, 0.0 and 99m Tc-pertechnetate, 0.9.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of the 99m Tc tricarbonyl was monitored by TLC on glass-backed silica gel 60 plates developed with 1% HCl in methanol 20. The R f values in this system are as follows: 99m Tc tricarbonyl, 0.2–0.8; 99m Tc colloids, 0.0 and 99m Tc-pertechnetate, 0.9.…”
Section: Methodsmentioning
confidence: 99%
“…Small aliquots of all 25 proteins were radiolabelled first for testing, following the recommendations on 99m Tc-tricarbonyl labelling given in [19]. Subsequently, larger aliquots were radiolabelled for imaging.…”
Section: Methodsmentioning
confidence: 99%
“…A number of laboratories have labeled antibody fragments bearing C-terminal (His) 6 tags with the [ 99m Tc(CO) 3 ] + synthon for SPECT imaging [4346]. Kogelberg, et al ., for example, labeled the α v β 6 -targeting diabody B6.3 via the coordination of [ 99m Tc(CO) 3 ] + to a C-terminal (His) 6 tag, and it was found that the resultant conjugate retained nanomolar affinity for its target and demonstrated tumor-specific targeting in vivo .…”
Section: Peptide Tagsmentioning
confidence: 99%